(untitled) (Research, Society and Development, 2022)
Palliative care are actions that enhance the quality of life of patients and their families in coping with a progressive and incurable disease. In this context, the role of Nursing stands out, which has contributed to the development of various terminologies related to the stages of the nursing process. Objective: To identify in the literature the main nursing diagnoses for patients in palliative care and classify them according to the Basic Human Needs of Horta. Methodology: This is an integrative literature review, data collection was performed in online databases: PubMed, CINAHL, Medline, LILACS, BDENF, IBECS. Delimitation period of the last 05 years, the descriptors “Palliative care” AND “Nursing diagnoses”, “Palliative care” AND “Nursing” were used. Results: The sample consisted of 7 articles. The most used classification system for formulating diagnoses was NANDA. 86 nursing diagnoses were identified, 46 in Psychobiological Needs; 35 in Psychosocial Needs and 05 in Psychospiritual Needs according to Horta’s theory.Conclusion: It is expected that this study can contribute to the realization of nursing care, subsidizing nursing interventions that aim to address the needs of patients under palliative care. It is believed that the statements of diagnoses classified in Horta’s theory serve as a subsidy for clinical nursing practice.